(untitled) (Research, Society and Development, 2021)
On August 7, 2014 was published the supplementary law 147 which changed the complementary law 123/2006 on the Statute of Micro and Small Enterprise and provides for the Simples Nacional. With the changes, from 2015 many types of services have been awarded the opportunity to participate in the simplified regime, among them the medical services. The work then aims to study a company of this specific targeting, showing through study if the option by the Simples Nacional is more advantageous than the current form of taxation (Lucro Presumido). About the methodology used, it refers to a descriptive research through case study and is characterized as the problem of a qualitative approach. The data were provided by the accounting firm responsible for the taxation of the company, granting it, which however did not allow the publication of his name and for this reason in the course of work will be referred to as Medicina do Trabalho Ltda. The company is located in Natal in Rio Grande do Norte, and operates in the market since June 2010, specializes in occupational health services with an emphasis on admission and dismissal exam. To achieve this task, he proposed to study tax avoidance through comparison of tax data of the year 2014, with the new simple table applied to the type of service - Annex VI. In the obtained analysis, it was demonstrated that despite the simplified taxation, the Simples Nacional is not always the most advantageous form of taxation financially.